2007
DOI: 10.1016/j.addbeh.2007.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Hook 'em horns and heavy drinking: Alcohol use and collegiate sports

Abstract: Heavy alcohol consumption has been associated with collegiate sporting events, but little is known about specific levels of consumption over the course of an entire sports season. Ongoing web-based daily-monitoring at the University of Texas at Austin allowed assessment of drinking levels of students (n = 541) over two full football seasons. High-profile football game days were among the heaviest days for alcohol consumption, comparable to consumption on other well-known drinking days such as New Years Eve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 16 publications
6
56
2
Order By: Relevance
“…According to Nelson et al (2010), availability can include alcohol sold within the stadium but also accessed with tailgate parties or fans bringing their own. With alcohol being highly common at sporting events, fans tend to consume drinks at extremely high levels (Glassman et al, 2007(Glassman et al, , 2010Neal and Fromme, 2007;Neal et al, 2005;Neighbors et al, 2006b). Neal and Fromme (2007) found that football games considered to be high profi le were often the heaviest drinking occasions, even when compared with celebrating alcohol-centered holidays like New Year's Eve or Halloween.…”
Section: Drinking Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nelson et al (2010), availability can include alcohol sold within the stadium but also accessed with tailgate parties or fans bringing their own. With alcohol being highly common at sporting events, fans tend to consume drinks at extremely high levels (Glassman et al, 2007(Glassman et al, , 2010Neal and Fromme, 2007;Neal et al, 2005;Neighbors et al, 2006b). Neal and Fromme (2007) found that football games considered to be high profi le were often the heaviest drinking occasions, even when compared with celebrating alcohol-centered holidays like New Year's Eve or Halloween.…”
Section: Drinking Contextsmentioning
confidence: 99%
“…With alcohol being highly common at sporting events, fans tend to consume drinks at extremely high levels (Glassman et al, 2007(Glassman et al, , 2010Neal and Fromme, 2007;Neal et al, 2005;Neighbors et al, 2006b). Neal and Fromme (2007) found that football games considered to be high profi le were often the heaviest drinking occasions, even when compared with celebrating alcohol-centered holidays like New Year's Eve or Halloween. With heavy alcohol use comes consequences, with the most commonly reported alcohol-related problem at sporting events being fi ghts inside and outside games (Lenk et al, 2009).…”
Section: Drinking Contextsmentioning
confidence: 99%
“…In an effort to improve interventions by targeting specifi c risk factors in this population, researchers have developed a stronger focus on "event-specifi c drinking," that is, drinking that occurs during specifi c events and activities that promote heavier than average levels of consumption (Neighbors et al, 2007). These events include one-time celebrations such as 21st birthday parties (Neighbors et al, 2005;Rutledge et al, 2008), weekly events such as football games and tailgating events (Neal and Fromme, 2007;Neighbors et al, 2006), and weeklong drinking events such as spring break (Grekin et al, 2007;Lee et al, 2009).…”
mentioning
confidence: 99%
“…Finally, a strength of ESM is reducing biases introduced by retrospective recall (Shiffman, 2009 always risk of reactivity effects or reluctance to self-disclose. Our procedure tried to maximize honest reporting and limited research supports the accuracy and lack of reactivity of ESM data (Neal & Fromme, 2007;Wray et al, 2012). …”
mentioning
confidence: 99%